Supply Chain Responsiveness in an Asian Global Electronic Manufacturing Firm: ABX Energy (M) - Veera Pandiyan Kaliani Sundram; Premkumar Rajagopal; Nur Atiqah Zahari Azar; Atikah Shamsul Bahrin; Gouri Appasamy (International Journal of Supply Chain Management, 2018)
The purpose of this study is to scrutinize the significance of supply chain strategies - Lean and agile supply chain - as well as the strategic supplier partnership towards improving the supply chain responsiveness in ABX Energy (M). All stated strategies show a simple logic that it does give impact on manufacturing firm like ABX Energy (M). A conceptual research model is constructed in demonstrating the firm that implement a proper supply chain practices to support and execute its supply chain strategy which will boost its responsiveness on the subject matter of supply chain. The collections of primary data are collected through interview with the managers. The study is carried out on qualitative data basis, which differs it with other research on this subject which most have been in quantitative form. An Asian global company, ABX Energy (M), is selected to investigate its responsiveness towards supply chain. The results from this research shows that it will greatly benefit the firm if the strategies of their supply chain being considered thoroughly. This paper aimed to raise a research subject that previously being held mostly in quantitative form and to further overcome the shortcoming in current debate beyond any previous description mentioned.